Organizational innovation factors, capabilities and organizational performance in Iranian automotive industry - Masoomzadeh, Ahmad (2020)
Understanding the relationship between innovation and performance of firms for both large and small organisations is relevant for researchers and policy-makers. Many firms and organisations have begun to recognise that innovation proficiency is the key to building a sustainable competitive advantage for their products or services in a progressively crowded marketplace. Even though defining innovation capability through its antecedents is considered as a unique methodology, a theoretical and comprehensive study about the effects of internal and external innovation drivers on organisational performance is still scarce. This study addresses the deficiency of empirical studies by developing a comprehensive model to examine the effects of external innovation drivers and internal innovation drivers namely organisational culture and intellectual capital on organisational performance directly and through innovation capability. A quantitative methodology is used to investigate the relationship paths. Data were collected from 275 companies in the automotive sector in Iran by using a cross-sectional survey method. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used in the hypotheses testing. The results indicate that internal and external organisational innovation has a positive and significant relationship with organisational performance directly and through organisational innovation. Fundamentally, the results of this study can assist organisations and academic bodies to expand their knowledge on the role of innovation drivers and the capability of organisational performance in automotive industry.